Gangguan Bahasa Pada Penderita Afasia - Bilqis Putri Anas; Choyrunisa Cahya Assago; Misya Lova Haqsya Afrilia Delvi; Wardah Nuranisa; Siti Hamidah (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
Aphasia is a communication problem caused by brain damage. This condition affects language skills in people with aphasia, resulting in obstacles in speaking, reading, writing and understanding language. This research aims to determine the development of language skills in people with aphasia and find ways to help them. The research method used is a systematic literature review (SLR) using a database from Google Scholar. The results of the research show that people with aphasia experience obstacles in understanding the meaning of language or in pronouncing words. Efforts that can be made to help aphasia sufferers include the use of information and communication technology (TIC), special education, and therapy. This research supports better and more effective treatment for people with aphasia